2010
DOI: 10.1590/s1806-37132010000300011
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da concentração de monóxido de carbono no ar exalado em tabagistas com DPOC

Abstract: OBJETIVO: Medir os níveis de monóxido de carbono no ar exalado (COex) em tabagistas com e sem DPOC. MÉTODOS: Tabagistas frequentadores dos ambulatórios do Hospital São Lucas em Porto Alegre (RS) entre setembro de 2007 e março de 2009 foram convidados a participar do estudo. Os participantes responderam a um questionário com características demográficas e epidemiológicas e realizaram espirometria, medição de cotinina urinária e de COex. Os participantes foram agrupados conforme a presença de DPOC. RESULTADOS: F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 16 publications
1
13
0
1
Order By: Relevance
“…In current smokers with COPD, it is difficult to discriminate between the amount of increased exhaled CO due to lung oxidative stress and that due to CO contained in cigarette smoke. [50] There was negative correlation between eCO levels in COPD patients and lung function (FEV1 values) and it was statistically significant ( P < 0.01), similar to previous study. [6] However, our results differ from a study that showed no negative correlation between CO levels and lung function.…”
Section: Discussionsupporting
confidence: 89%
“…In current smokers with COPD, it is difficult to discriminate between the amount of increased exhaled CO due to lung oxidative stress and that due to CO contained in cigarette smoke. [50] There was negative correlation between eCO levels in COPD patients and lung function (FEV1 values) and it was statistically significant ( P < 0.01), similar to previous study. [6] However, our results differ from a study that showed no negative correlation between CO levels and lung function.…”
Section: Discussionsupporting
confidence: 89%
“…While it is known that quitting smoking is the only factor that can slow the progression of this disease, there is no evidence that there exists a reversion for the pulmonary impairment that has already began. Approximately 90% of COPD cases are related to smoking, whereas other less common risk factors include occupational exposure and biomass burning (26),(27),(28). The historical finding of a lower prevalence of COPD in the female population is associated with a lower proportion of smokers in this group.…”
Section: Introductionmentioning
confidence: 99%
“…They suggest that multidimensional dyspnea scales should be applied in the evaluation of COPD patients. Chatkin et al93 measured exhaled carbon monoxide (COex) levels in smokers with and without COPD. which did not differ significantly between smokers with COPD and those without, suggesting that there seems to be no major contraindications to their use in smokers with COPD.…”
Section: Introductionmentioning
confidence: 99%